(untitled) (Heritage, 2025)
The onographic study Origins of Poetry. Ritual and Myth in Oral Poetry is one in a series of valuable folklore studies published in the Literature and Language edition of the Society for the Serbian Language and Literature of Serbia.Based on a rich and extensive reference literature (see pp. 289-307), this study by the distinguished folklorist Prof. Dr. Snezana Samardžija offers answers to a number of important questions in the profession - teachers of the Serbian language (and literature), which are listed in the note at the end of the book (see pp. 287-288): ritual and customary lyrical folk songs; mythological songs; study of variants of epic songs;ethical problems arising from changing sensibilities in patriarchal and contemporary society; Saint Sava in folk literature; terminology in folk literature; women in folk poetry;recitation of epic folk songs; comparative reading of the folk epic song Banović Strahinja and the play Mihiz by Borislav Mihajlović.